Theory of Electron Transport in Semiconductors A Pathway from Elementary Physics to Nonequilibrium Green Functions - Jacoboni, Carlo. (Springer Series in Solid-State Sciences,, 2010)
This book describes in details the theory of the electron transport in the materials and structures at the basis of modern micro- and nano-electronics. It leads and accompanies the reader, through a step-by-step derivation of all calculations, from the basic laws of classical and quantum physics up to the most modern theoretical techniques, such as nonequilibrium Green functions, to study transport properties of both semiconductor materials and modern low-dimensional and mesoscopic structures.